Controlling the Shape of Evaporating Droplets by Ionic Strength: Formation of Highly Anisometric Silica Supraparticles1. Issue 2 (25th November 2013) - Sperling, Marcel; Velev, Orlin D.; Gradzielski, Michael
Abstract Anisometric silica supraparticles are produced by a simple process of evaporation of sessile droplets containing fumed silica deposited on a superhydrophobic substrate. The shape of the supraparticles is directly controlled by the salt (NaCl) concentration, becoming anisometric beyond a threshold concentration, as quantified by light microscopy. This process is easily extended to supraparticles containing further functional colloidal components.